Алексей Надежкин, Проблема вариативности переводов Библии на примере анализа пс. 2:12 - Береснева, Людмила; Надежкин, Алексей (Acta Polono-Ruthenica, 2021)
This study is devoted to the problem of the appearance of variants in the translation of the text of the Holy Scriptures on the example of the analysis of Ps. 2:12. The aim of the study is to find out the reason for the occurrence of discrepancies in the translation of this psalm. The significance of the work lies in identifying the genesis of modern Russian translations of Ps. 2:12, as well as the reasons for linguistic difficulties that arise when translating the Hebrew and Greek Psalms into other languages. The results of the research may be used when translating and commenting on the studied text. The main conclusion is that the reason for the appearance of a “dark” place for the modern reader in the second psalm – “Accept the punishment, may the Lord not be angry” – stems from the polysemy of the Greek word “παιδείας”, which can be translated as “education, training, culture’ as well as “youth”. The Hebrew translators have interpreted this verse as “worship purely”, “worship with purity”, “arm yourself with purity”. Some of the translation options for this verse are based on the Septuagint, which gives a literal translation into Greek of the Hebrew text: “Accept / keep the lesson”. The variety of translation options for Ps.2:12 results from the polysemy in the Hebrew language, superimposed on the borrowed meaning of the word “bar” from the Chaldean language and on the Greek ambiguity in the recipient language; later on, the complexity of this verse increased even more due to the literalism of the Church Slavic translation. The value of this research lies in comparing the variants of the Russian translations of Ps. 2:12 and clarifying their history.